TRADISI-TRADISI ISLAM MELAYU DI NUSANTARA (INDONESIA) - Maryamah; Muhammad Akbar Hilmi; Elya Kumala Sari; Keysha Alea Amanah Fatiha (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
In the middle of the vast blue ocean, under the hot tropical sun, lies the archipelago of the archipelago, which is home to extraordinary cultural diversity. One of the distinctive aspects of the archipelago's cultural heritage is the Malay Islamic traditions that have developed over the centuries. This article will take you on a journey to explore these traditions, which shape the identity and culture of the people of this region. In the group of islands stretching from Sumatra to Maluku, Islam has played an important role in shaping social, religious and artistic norms. These traditions reflect not only strong Islamic roots but also unique adaptations to the environment and culture. local. They created a rich cultural network, which still influences the daily lives of people in the archipelago to this day. This research uses library research or literature study methods. Researchers use a lot of literature to collect data and use a qualitative approach because the data produced is in the form of words and descriptions. Malay traditions are habits that have been carried out for a long time in Malay areas and are part of the life of a community group. What is certain is that these habits include cultural values, norms, laws and regulations that are interrelated with these habits. Malay traditions are habits that have been carried out for a long time in Malay areas and are part of the life of a community group.